Effect of Organic Solvents on Microalgae Growth, Metabolism and Industrial Bioproduct Extraction: A Review - Miazek, Krystian; Kratky, Lukas; Sulc, Radek; Jirout, Tomas; Aguedo, Mario; Richel, Aurore; Goffin, Dorothee (International journal of molecular sciences, 2017)
In this review, the effect of organic solvents on microalgae cultures from molecular to industrial scale is presented. Traditional organic solvents and solvents of new generation-ionic liquids (ILs), are considered. Alterations in microalgal cell metabolism and synthesis of target products (pigments, proteins, lipids), as a result of exposure to organic solvents, are summarized. Applications of organic solvents as a carbon source for microalgal growth and production of target molecules are discussed. Possible implementation of various industrial effluents containing organic solvents into microalgal cultivation media, is evaluated. The effect of organic solvents on extraction of target compounds from microalgae is also considered. Techniques for lipid and carotenoid extraction from viable microalgal biomass (milking methods) and dead microalgal biomass (classical methods) are depicted. Moreover, the economic survey of lipid and carotenoid extraction from microalgae biomass, by means of different techniques and solvents, is conducted.
Keywords: mikrořasy; extraction; cultivation; Solvents; microalgae; Chemical Industry; rozpouštědla; biomasa; Energy Metabolism; průmyslový odpad; organic solvents; energetický metabolismus; organické látky; Organic Chemicals; Industrial Waste; chemický průmysl; industrial compounds; Biomass; economic survey; Microalgae; industrial effluents